Effect of Supplementing Lawsonia Inermis on Chicken Ovary and Egg Quality Parameters - Ahmad, Tufail; Hussain Leghari, Imdad; Bashir, Anam; Ali Laghari, Farhan; Ahmed Solangi, Irfan; Zain Khosa, Sumbal; Marri, Naseeb Ullah; Mujeeb Ur Rehman; Muhammad Ishaq; Israr ul Hussain; Marri, Naik Muhammad; Inam, Zeeshan; et al. (Indus Journal of Bioscience Research, 2024)
The effects of Lawsonia inermis (henna) on the egg quality parameters of White Leghorn chickens over a 4-week period. A total of 25 chickens were housed individually, with free access to feed and water. The results showed notable variations in egg quality attributes due to the supplementation of L. inermis. In terms of albumen height, the control group had the highest measurement (8.01 cm), while Group C recorded the lowest (7.46 cm). The albumen index was also highest in the control group (2.43) and lowest in Group B (2.29). Group D had the longest albumen length (92.86 mm), while Group B had the shortest (89.09 mm). Egg weight was heaviest in the control group (67.78 g) and lightest in Group B (58.21 g). The Haugh unit was highest in Group B (87.63 HU) and lowest in Group C (85.73 HU), while shell thickness was thickest in the control group (2.66 mm) and thinnest in Group E (0.42 mm). Yolk measurements showed Group D had the largest yolk diameter (43.14 mm), while Group B had the smallest (41.11 mm). Yolk height was tallest in Group B (17.58 mm) and shortest in the control group (17.28 mm). Reproductive parameters, including follicle weights, were significantly affected, with Group A showing the highest weights across several follicle categories, while Group E recorded the lowest. The length of reproductive organs varied, with the control group having the longest shell gland (9.75 cm) and reproductive tract length (70.85 cm), and Group E showing the shortest. Lawsonia inermis supplementation affected several egg quality parameters, including shell strength and yolk color. Although these changes were consistent with prior studies, the results did not indicate substantial alterations in egg quality due to L. inermis.